The Relationship Between Eating Patterns With Anemia Status In Adolescent Girls At Mtsn 1 Deli Serdang - Mahdiah; Alvisyahrani, Tazkia; Friscillia, Sonya (Indonesian Scientific Publication, 2023)
Anemia is a condition where the number of red blood cells or hemoglobin (Hb) levels in the blood is lower than normal according to age and gender. To find out the relationship between eating patterns and to find out the relationship between breakfast and anemia status in young women. The design method in this research isCross Sectional. The population is all young women at MTSN 1 Deli Serdang. The sampling in this research was purposive sampling. Data collection was carried out using interviewssemi quantitative food frequency questionnaire as a research instrument. Data processing through editing, coding, data entry, tabulating. Using the Chi Square test. The results of the study showed that 34.3% of teenagers had a variety of eating types, and 89.3% of teenagers with non-diverse eating types. Adolescents with a frequency of eating >3 times/day were 37.5%. The frequency of eating and eating <3 times/day is 90.4%. The number of teenagers who eat well is 35.7%, and the number of teenagers who eat poorly is 14.3%. Types of eating breakfast in the diverse category were 50.8%, and types of eating were not diverse as much as 49.2%. The frequency of eating in the category once a day was 50.7%, and the frequency of eating in the category <3 times a week was 49.2%. The number of meals in the good category was 50.8%, the sufficient category was 20.6% and the number of meals in the poor category was 28.6%. Anemia status in the anemia category was 23.8%, and anemia status in the non-anemia category was 76.2%. There is a relationship between eating patterns and breakfast (type, frequency, amount) with anemia status at MTSN 1 Deli Serdang.